Draft Annual Plan 2004-2005 Volume-I Sector: Agriculture and Allied Activities Andaman and Nicobar Administration - Planning Commission (Planning Commission, 2004)
Paddy is the main crop grown during Kharif in about 25% of the land available for agricultural purpose. the rice area is mainly restricted in Andaman District where about 11,500 ha. is cultivated under paddy. This area is also utilized for pulses, oilseeds and vegetables in Rabi after harvest of paddy. Such crops are grown under rainfed condition due to lack of proper irrigation facilities. Growing two successive crops of paddy is not common. Therefore, to increase production per unit area, scientific package of practices, utilization of quality seeds, timely supply of inputs, PP Measures coupled with better management and care are the options to be practiced in an integrated manner by the farmers in these Islands. Vegetables are getting popular of late and some vegetables are now grown almost throughout the year in flat paddy lands.
Andaman and Nicobar Administration, Planning Department